Characterisation of gut mucosa in patients with potential coeliac disease - Mohamed, Bashir Mustafa Y (Trinity College (Dublin, Ireland). Department of Immunology, 2007)
Coeliac disease is a gluten dependent enteropathy with a high incidence and increased risk of mortality. Diagnosis of coeliac disease is based on a biopsy of small intestine. However, it is now believed that many individuals have gluten- sensitive inflammation without an overt small intestinal lesion. Endomysial antibodies (EMA) ai'e widely used to screen for coeliac disease with 100% specificity and 89-100% sensitivity. These antibodies do not only support the diagnosis, but also predict the severity of mucosal damage in patients with gluten-sensitive enteropathy (GSE). The aim of this thesis was to examine a group of patients (25 patients) with a positive EMA test in the absence of supportive histological evidence for coeliac disease: these patients are known throughout the manuscript as the study group subjects (SGS). Immunohistochemical techniques were used to characterise intestinal T cell subpopulations in these patients and the results were compared with patients with established coeliac disease and with normal control population. The study group subjects showed significantly increased numbers of intraepithelial lymphocytes (lELs) expressing CD2, CD3, CD7, CDS, and CD69 compared with the normal control group. In addition, the number of proliferating crypt cells in the study group subjects detected by the Ki67 antibody was evaluated. It was shown that crypt cell proliferation in the study group subjects was increased compared with the normal control group, suggesting active cell proliferation.
Keywords: Immunology, Ph.D.; Ph.D. Trinity College Dublin